The Role of Digital Banking in Strengthening Service Quality and Competitiveness in Islamic Banking: A Case Study in Lubuklinggau - Raju Subkarima; Novita Sari Sari; Liliany Purnama Ratu (Utan Kayu Publishing, 2025)
AbstractThe rapid advancement of digital technology has significantly transformed service delivery in the banking sector, including Islamic banking institutions. This study examines the role of digital technology in enhancing service quality at Bank Sumsel Babel Syariah, Lubuklinggau Branch, focusing on both customer and institutional perspectives. Using a qualitative case study design, data were collected through in-depth interviews, direct observations, and document analysis with bank staff and active digital service users. The findings reveal that digital banking adoption—particularly mobile banking, internet banking, and Automated Teller Machines (ATMs)—has improved service accessibility, transaction security, and transparency, while also increasing operational efficiency, stimulating service innovation, and strengthening competitiveness. However, challenges such as low digital literacy, data security concerns, limited internet access, high maintenance costs, and uneven staff digital skills remain. This study contributes to the literature by integrating dual perspectives, emphasizing the interplay between human capital and technological adoption in semi-urban Islamic banking contexts. The results underscore the need for targeted customer education, continuous staff training, and infrastructure improvements to maximize the benefits of digital transformation in Islamic banking.